Chairperson succession : competences, moderators, and disclosure - Germann, Cornel (Springer Gabler, 2023)
This open access book empirically analyses the competences (input), moderators (process), and disclosure (output) of board chair succession practices for publicly listed organisations in Switzerland. As primus inter pares (Latin for first among equals), the chair of the board of directors holds a unique organisational position. For fulfilling the non-transferable duties pursuant to Article 716a revCO, it is essential that the chair is a person who has rational economic and socio-emotional skills. To date, however, it is unclear how organisations structure the search for a chairperson. On the one hand, this ambiguity arises from a legal perspective, as succession-related formal regulations (hard law) or best-governance principles (soft law) are rare and often lack specificity, and, on the other hand, from a business perspective, as there is a lack of sufficient attention and diligence. Previous research on board governance has primarily focused on the dyadic relationship between board composition and organisational performance (board effectiveness research). However, as board succession is a dynamic process, the research focus should go beyond a pure output/performance paradigm.
Keywords: Boards of directors -- Switzerland.; Executive succession -- Switzerland.; Corporate governance -- Switzerland.; Conseils d'administration -- Suisse.; Cadres (Personnel) -- Relève -- Suisse.; Gouvernement d'entreprise -- Suisse.; Boards of directors; Corporate governance; Executive succession; Switzerland